Development of Qur'an Hadith Module Based on Contextual Approach to Improve Students' Critical Thinking Skills at MAN 5 Hulu Sungai Tengah - Khairun Nisa; Akhmad Rahim Mubtadi (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to develop a contextual approach-based Al-Qur'an Hadith module with the theme